VASCULAR PATTERNS AND MORPHOLOGY IN DERMOSCOPY - PART I. BASIC PRINCIPLES - Laureano, André; Fernandes, Cândida; Cardoso, Jorge (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
Dermoscopy is a noninvasive, in vivo technique that increases the diagnostic accuracy in both melanocytic and nonmelanocytic skin tumors. In nonpigmented tumors allows the visualization of vascular structures not visible to the naked eye. Part I of this article discusses the dermoscopic evaluation of nonpigmented skin tumors including basic principles of specific morphologic types and architectural arrangement of vessels and the presence of additional dermoscopic clues.